Synthesis and Crystal Structure of Cobalt(II) Complex of 4,4?-Diamino-1-[(cyclohexa-2,4-dienyl)methyl]benzene - Mei, Zhenhua; Niu, Xiang; Sun, Jie; Qu, Bin (Asian Journal of Chemistry, 2010)
The crystal structure of cobalt(II) complex of 4,4′-diamino-1- [(cyclohexa-2,4-dienyl)methyl]benzene has been determined by single crystal X-ray diffraction method. The crystal belongs to orthorhombic system, space group P1 with unit cell constants a = 9.2500(8), b = 11.6619(10), c = 11.9660(11) Å, V = 1273.36(19) Å3, Z = 1, Dc = 1.363 g/cm3, μ = 0.406 mm-1, F(000) = 550, R and wR are 0.0499 and 0.1498, respectively for 5981 unique reflections with 5095 observed reflections (I > 2σ(I)). In the crystal structure, molecules are linked into chains along the a axis by N–H···O intermolecular hydrogen bonds along the a axis.